(untitled) (Al-Qamar, 2022)
This article studies the methodology of Masābīh al-Jamʻ, a commentary on Sahīh al-Bukhārī by Imām Abu Bakr Damāmīnī, along with a brief account of its author. It argues that this book is considered to be one of the most important commentaries of Sahīh al-Bukhārī, which has arranged to explain Gharīb words, solutions to Arabic problems, explanation of the ambiguities of isnads, lexical, syntactical and principled advantages and other points. Imām Damāmīnī has made valuable additions to the dictionary, eliminated the defects found in the commentaries before him. It is a simple and syntactic book. Damāmīnī has followed the tradition of Zarqalī in choosing the hadiths and spoke on the hadiths. Damāmīnī made special use of "Al-Tawzih" by Ibn al-Mulqqin, Jalal al-Din Ibn al-Balqīnī’s book "Al-Ifhām lima Waqa fi Bukhārī min al-Ibhām" and "Al-Tanqīh of al-Faz Al-Jāmʻ al-Sahih" by Imam Zarkashi. The Study reveals that about three thousand hadiths has been interpreted by Damāmīnī.